1995
DOI: 10.1002/kin.550270805
|View full text |Cite
|
Sign up to set email alerts
|

Laser photolysis studies of hydrazine vapor: 193 and 222‐nm H‐atom primary quantum yields at 296 K, and the kinetics of H + N2H4 reaction over the temperature range 222–657 K

Abstract: The primary quantum yield of H-atom production in the pulsed-laser photolysis of hydrazine vapor, N2H4 + h v + H + NzH3, was measured to be (1.01 2 0.12) at 193 nm relative to HBr photolysis, and (1.06 2 0.16) at 222 nm relative to 248-nm NzH4 photolysis, in excess He buffer gas a t 296 K. The H-atoms were directly monitored in the photolysis by cw-resonance fluorescence detection of H('S) at 121.6 nm.The high H-atom yield observed in the photolysis is consistent with the continuous ultraviolet absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…13,40,48 Our experiments have shown that the removal of a single H atom is a minor process, and as might be expected we see excitation into the new bond of the reaction product in the form of vЉϭ1 and 2 OH vibrations. Of the total initial OH yield measured, we estimate that ϳ50% is distributed in the ground vibrational state.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…13,40,48 Our experiments have shown that the removal of a single H atom is a minor process, and as might be expected we see excitation into the new bond of the reaction product in the form of vЉϭ1 and 2 OH vibrations. Of the total initial OH yield measured, we estimate that ϳ50% is distributed in the ground vibrational state.…”
Section: Discussionsupporting
confidence: 78%
“…The flow-tube rate coefficients, k 3 , measured in the temperature range 252-372 K were in excellent agreement with those measured in our pulsed-photolysis reactor. 40 The fact that we obtain similar rate coefficient values in two different apparatuses suggest that there are no significant systematic errors in determining the various flow-tube parameters which are required to deduce the second-order rate coefficients from the measured pseudo-first-order ͓O͑ 3 P͔͒ decays. The precision of the individually measured second-order rate coefficient, k 1 , may be derived from the standard propagation of random error analysis of the various flow-tube parameters that determine k 1 .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…To minimize the interference effect from secondary radical chemistry in our N 2 H 3 + NO 2 rate coefficient measurements, the initial radical photochemistry was carefully controlled. Equations , , , , , and – below show the important chemical reactions relevant to the present analysis. The first-order wall loss rates for eqs – are expected to be typically in the 1–20 s –1 range for the present flow-tube setup . Photolysis through eq provides the primary source for the N 2 H 3 radicals in the experiment, though secondary production is possible via eqs and .…”
Section: Results Of Experimentsmentioning
confidence: 99%